The didactic divide and the education of teachers of mathematics in Sweden - Bergsten, Christer; Grevholm, Barbro (NOMAD Nordic Studies in Mathematics Education, 2004)
On a background of tradition versus renewal, a discussion on recent teacher education reforms in Sweden is given. A balance of different aspects of content and a need for research are seen as critical for the formation of mathematics teacher education. A conception of a ’didactic divide’ between disciplinary and pedagogical knowledge is used as an analytic tool to describe the rationale behind the design of the reforms. Empirical data from student teachers enrolled in the new teacher education programme highlight how the structure and content of the programme contribute to overcoming the divide.